IGARSS 2019 - 2019 IEEE International Geoscience and Remote Sensing Symposium 2019
DOI: 10.1109/igarss.2019.8898362
|View full text |Cite
|
Sign up to set email alerts
|

Landsat 9: Mission Status and Prelaunch Instrument Performance Characterization and Calibration

Abstract: Landsat 9 is currently under development as a joint effort between NASA and the United States Geological Survey (USGS). Landsat 9 is essentially a rebuild of Landsat 8 and has the same two sensors, the Operational Land Imager (OLI) and the Thermal Imaging Sensor (TIRS). The OLI-2 on Landsat 9, is being built by Ball Aerospace and has completed its pre-launch characterization and calibration and is scheduled to be delivered in the summer of 2019. The TIRS-2, being built by Goddard Space Flight Center, is curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It is indeed likely that in the future this data set will primarily be useful for providing decadal context to those from improved sensors. CWS will only increase in importance given recent and future datasets that represent improved height and inundated area measurements from sensors such as Planet, Sentinel −2, Landsat 8 + 9 and the upcoming Surface Water and Ocean Topography mission (Boshuizen et al., 2014; Drusch et al., 2012; Fu et al., 2009; Markham et al., 2019; Roy et al., 2014). As Durand et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is indeed likely that in the future this data set will primarily be useful for providing decadal context to those from improved sensors. CWS will only increase in importance given recent and future datasets that represent improved height and inundated area measurements from sensors such as Planet, Sentinel −2, Landsat 8 + 9 and the upcoming Surface Water and Ocean Topography mission (Boshuizen et al., 2014; Drusch et al., 2012; Fu et al., 2009; Markham et al., 2019; Roy et al., 2014). As Durand et al.…”
Section: Discussionmentioning
confidence: 99%
“…The Landsat 9 OLI onboard radiometric calibration system is identical to that of Landsat 8 OLI, and the various subsystems include a shutter for dark measurements, two solar diffusers (working and pristine), two stimulation lamp assemblies, and the ability to view the moon through a spacecraft maneuver [2,5]. As with the Landsat 8 OLI, the Landsat 9 OLI underwent a rigorous pre-launch calibration and characterization process [6][7][8][9][10].…”
Section: Bandmentioning
confidence: 99%
“…SNPP VIIRS, NOAA-20 VIIRS, Landsat-8 OLI, and Landsat-9 OLI were calibrated prior to the launch with traceability to the radiance standard of the National Institute for Standards and Technology (NIST). The prelaunch test for these sensors indicated that their radiometric and spectral performance met specifications [21][22][23][24]. Multiple on-orbit calibration approaches have been implemented for both OLI and VIIRS to monitor and correct for changes in the radiometric response of the sensors [25][26][27][28].…”
Section: Data Products Used In the Studymentioning
confidence: 99%